1997
DOI: 10.2165/00003088-199732040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Naproxen

Abstract: Naproxen is a stereochemically pure nonsteroidal anti-inflammatory drug of the 2-arylpropionic acid class. The absorption of naproxen is rapid and complete when given orally. Naproxen binds extensively, in a concentration-dependent manner, to plasma albumin. The area under the plasma concentration-time curve (AUC) of naproxen is linearly proportional to the dose for oral doses up to a total dose of 500 mg. At doses greater than 500 mg there is an increase in the unbound fraction of drug, leading to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 93 publications
3
81
0
4
Order By: Relevance
“…Second, NSAIDs are used therapeutically at doses that produce more than a 50% reduction in prostanoid formation. Indeed, a survey of the literature established that, for diclofenac (10), etodolac (11), indomethacin (12,13), fenoprofen (12), flurbiprofen (14), ketoprofen (12), ketorolac (13,15), meclofenamate (12), meloxicam (16), naproxen (17), nimesulide (18), piroxicam (19), sulindac (20), and tolmetin (12), the steady-state plasma concentrations of these drugs, as well as the peak concentrations of aspirin (12), would produce average inhibitions in our assay systems of 82 Ïź 5% (COX-1), 74 Ïź 5% (WBA-COX-2), and 89 Ïź 2% (WHMA-COX-2) (n Ï­ 15). Comparison of the potencies of the NSAIDs against COX-1 and COX-2 at the IC 80 value, therefore, appears more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, NSAIDs are used therapeutically at doses that produce more than a 50% reduction in prostanoid formation. Indeed, a survey of the literature established that, for diclofenac (10), etodolac (11), indomethacin (12,13), fenoprofen (12), flurbiprofen (14), ketoprofen (12), ketorolac (13,15), meclofenamate (12), meloxicam (16), naproxen (17), nimesulide (18), piroxicam (19), sulindac (20), and tolmetin (12), the steady-state plasma concentrations of these drugs, as well as the peak concentrations of aspirin (12), would produce average inhibitions in our assay systems of 82 Ïź 5% (COX-1), 74 Ïź 5% (WBA-COX-2), and 89 Ïź 2% (WHMA-COX-2) (n Ï­ 15). Comparison of the potencies of the NSAIDs against COX-1 and COX-2 at the IC 80 value, therefore, appears more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Although unbound plasma concentrations of NSAIDs-Glu have not been previously reported, total plasma concentrations of glucuronide conjugates of diclofenac (1.8±0.5 ”M), 24) ibuprofen (3.6±2.0 ”M), 23) naproxen (undetectable) 35) and flurbiprofen (undetectable) 36) have been determined after administration of clinical doses. Therefore, considering plasma concentration and inhibitory potencies, it is unlikely that NSAIDs-Glu other than diclofenac glucuronide inhibit OAT3-mediated MTX uptake at clinical doses.…”
Section: Resultsmentioning
confidence: 99%
“…21,22) Most NSAIDs-Glu molecules are excreted directly into urine. 23,24) Recently, our laboratory reported that NSAIDs-Glu, as well as parent NSAIDs, are involved in inhibition of urinary excretion of MTX via MRP2 and MRP4. 25) Since the IC 50 of NSAIDs-Glu for MTX transport via MRPs was lower than that of parent NSAIDs, our results suggested that NSAIDs-Glu likely contribute to elevating the plasma concentration of MTX.…”
mentioning
confidence: 99%
“…Metabolic acidosis and shock have been reported in massive ibuprofen overdose [23,24]. Naproxen is a weak acid with a pKa 4.15 [25]. The most plausible explanation for our patient's early acidosis was the large amount of ingested naproxen as well as its metabolites, considering they are also weak acids.…”
Section: Discussionmentioning
confidence: 67%
“…Lactic acidosis has been reported before in massive ibuprofen overdose including fatal cases [16,26]. Although naproxen is a weak acid, there is no evidence suggesting that urinary alkalinization can enhance elimination, possibly due to its high protein binding [25].…”
Section: Discussionmentioning
confidence: 99%